Nasal polyps in children - Karlida, T.; Keles, E.; Alpay, H. C.; Kaygusuz, I.; Yalcin, S.; Tazegul, A. (Galenos Yayincilik, 2007)
Objectives: Nasal polyps in the children are uncommon and its etiology is unclear. The purpose of this study is evaluation the alternatives of treatment, histopathological and clinical features of nasal polyposis which in pediatric population, in the light of literature. Methods: From 1997 to 2005, 23 patients (17 male, 6 female) whose ages between 6-17 years (mean age 11.2 years) who diagnosed as nasal polyp and treated surgically were included to the study. The charts of patients were reviewed retrospectively about the symptoms and findings, the localizations and types of the polyps, the radiological status, the surgical approaches, the follow-up duration and the recurrence. Results: The most common symptom was nasal obstruction (91.3%). The other symptoms were nasal discharge (56.6%), postnasal discharge (52.1%), snoring (47%) and facial pain (26%). By physical examination; bilateral polyps in 10 patients (43%), unilateral polyp in seven patients (30.4%) and choanal polyp in six patients (26%) (antrachoanal in 5 and sphenochoanal in one) were determined. On paranasal sinus CT investigation; pansinusal pathology in 8 patients, ethmoid and maxillary sinuses pathologies in 8 patients, maxillary sinus pathologies in 5 patients, bilateral isolated ethmoid sinus pathology in one patient and isolated sphenoid sinus in one patient were observed. The expanding of sphenoid sinus ostium and the removing of mucosa which origin of nasal polyps in one patient, Caldwell-Luc procedure in two patients, endoscopic surgery combined with Caldwell-Luc procedure in three patients, intranasal polypectomy in four patients and endoscopic surgery in 13 patients were performed. Postoperative bleeding was seen observed in one patient as complication. On histopathological evaluation; polyp characterized with atypic stroma in two patients (8.6%), allergic polyp in three patients (13%) and inflammatory polyp in 18 patients (78.2%) were diagnosed. The postoperative follow-up durations were between 2-48 months (mean 15 months). The recurrence occurred in three patients. Conclusion: Inflammatory polyps are the majority of pediatric nasal polyps. The surgical approach is effective and safety treatment method for pediatric nasal polyp.
Keywords: Nasal polyps; child; histopathology; treatment